2010
DOI: 10.1002/ldr.971
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cotton geotextiles on soil and water losses from Mediterranean rainfed agricultural land

Abstract: High soil erosion risk of Mediterranean cultivated soils is due to steep slopes, high rainfall intensities and low vegetation cover. Traditional land management as ploughing and herbicides give rise to high soil erosion rates. This paper reports on the use of a cotton geotextiles to control soil and water losses on agricultural land under Mediterranean climatic conditions. Eight paired plots (1, 2, 4 and 16 m 2 ) were studied during 1-year period under natural rainfall. Forty rainfall simulations under wet and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 29 publications
0
72
1
2
Order By: Relevance
“…The most common soil management techniques in Mediterranean countries consist of tillage (mechanical weeding) and no-tillage (chemical weeding) operations (García-Orenes et al, 2009), and both of them generally result in bare soils during the entire year Lasanta and Sobrón, 1988;Vaudour et al, 2015). However, alternative and more conservation-minded soil management practices have also been used like catch crops (Bonfante et al, 2015;García-Orenes et al, 2009), mulching (Jordán et al, 2011;Costantini et al, 2015), hydromulching (Prats et al, 2013), geotextiles (Giménez-Morera et al, 2010), natural grassing (Raclot et al, 2009) and rock fragments (Blavet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The most common soil management techniques in Mediterranean countries consist of tillage (mechanical weeding) and no-tillage (chemical weeding) operations (García-Orenes et al, 2009), and both of them generally result in bare soils during the entire year Lasanta and Sobrón, 1988;Vaudour et al, 2015). However, alternative and more conservation-minded soil management practices have also been used like catch crops (Bonfante et al, 2015;García-Orenes et al, 2009), mulching (Jordán et al, 2011;Costantini et al, 2015), hydromulching (Prats et al, 2013), geotextiles (Giménez-Morera et al, 2010), natural grassing (Raclot et al, 2009) and rock fragments (Blavet et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nuestra conclusión es afín a desestimar esa posibilidad, al menos, en la provincia de Málaga y, más concretamente, en nuestra área de estudio. Esto es atribuido a que: i) existen numerosos errores de identificación de suelos por la parte de la fuente edafológica utilizada en la provincia de Málaga; ii) confiamos en que las características químicas y físicas del suelo son irrepetibles en diferentes contextos espacio-temporales y virtualmente irreproducibles (Keestra et al, 2007;Keestra et al, 2009;Giménez Morera et al, 2010;Zhao et al, 2013;Xiao et al, 2015). Esta línea sería una cuestión importante para profundizar en el futuro como sugieren Liess et al (2012), incorporando herramientas de clasificación de suelos de FAO-WRB como los horizontes de diagnóstico.…”
Section: Discussionunclassified
“…Similar results were reached by Khan and Binoy (2012), Shao et al (2014) and Sutherland and Ziegler (2007; see Table 1). On the contrary, some studies (both field and laboratory) concluded that GTXs increase the run-off volume (Álvarez Mozos et al, 2014;Giménez-Morera et al, 2010;Kertézs et al, 2007). The increase might be caused by a dense cover of GTXs (Mitchel et al, 2003) or high slope gradient, where water can flow through the GTX fibres without infiltration into the soil (Álvarez-Mozos et al, 2014).…”
Section: Run-off Volume Reductionmentioning
confidence: 99%